DAMPAK PENGGUNAAN TEKNOLOGI FINTECH PADA INDUSTRI PERBANKAN DAN KEUANGAN BANK MANDIRI 2018-2022 - Gina Sonia; Syamsul Huda (STIE PGRI Dewantara Jombang, 2024)
This research aims to analyse the impact of the use of fintech technology on the banking and financial industry of Bank Mandiri in the period 2018-2022. The research method used is descriptive qualitative with a literature review approach. Data was collected from written sources such as journals, books, and Bank Mandiri documents related to the use of fintech technology in its operations. The results showed that the use of fintech technology in Bank Mandiri's banking and finance industry has had a significant positive impact. Fintech technology has helped Bank Mandiri to serve customers more efficiently and provide a better user experience. In addition, this technology has also improved the security and speed of transactions, thus providing high confidence for customers to use Bank Mandiri services. However, the use of fintech technology also has negative impacts, such as increased security risks and customer privacy, as well as creating injustice for people who do not have access to such technology. Therefore, Bank Mandiri needs to pay attention to aspects of risk and security arrangements related to the use of fintech technology.